Analisis Perkembangan Kemampuan Bahasa Anak Usia 4-5 Tahun Menggunakan Metode Read Aloud - Jubaidah, Siti; Sukrin, Sukrin; Ferdiansyah, Ferdiansyah (Arfah BHMS Foundation, 2025)
The development of language skills in early childhood is very important to prepare them for the challenges of further education. One effective method to develop children's language skills is the Read Aloud Method. This research was conducted at PAUD OI Balu to analyze the extent to which the application of the Read Aloud Method can affect the development of children's language skills aged 4-5 years. This research uses a qualitative approach with descriptive research type. Data collection techniques were conducted through direct observation, interviews with teachers, and documentation of learning activities in the classroom. Data sources in this study consisted of teachers who teach at PAUD OI Balu and 20 students aged 4-5 years who were involved in Read Aloud sessions. The research procedure involved observation of story reading activities, question and answer, group discussion, use of picture books and dramatization techniques applied by the teacher. The data analysis technique used was thematic analysis, in which the researcher identified patterns of children's language development based on the results of observations and interviews. The results showed that the Read Aloud Method had a positive effect on the development of children's language skills. A total of 60% of students showed good development in vocabulary, speaking ability, and story comprehension. Meanwhile, 25% of students were in the moderate development category, and 15% of students needed more intensive assistance to improve their language skills.